Hot Branching Dynamics in a Light‐Harvesting Iron Carbene Complex Revealed by Ultrafast X‐ray Emission Spectroscopy. Issue 1 (31st October 2019) - Tatsuno, Hideyuki; Kjær, Kasper S.; Kunnus, Kristjan; Harlang, Tobias C. B.; Timm, Cornelia; Guo, Meiyuan; Chàbera, Pavel; Fredin, Lisa A.; Hartsock, Robert W.; Reinhard, Marco E.; Koroidov, Sergey; Li, Lin; et al.
Abstract: Iron N‐heterocyclic carbene (NHC) complexes have received a great deal of attention recently because of their growing potential as light sensitizers or photocatalysts. We present a sub‐ps X‐ray spectroscopy study of an Fe II NHC complex that identifies and quantifies the states involved in the deactivation cascade after light absorption. Excited molecules relax back to the ground state along two pathways: After population of a hot 3 MLCT state, from the initially excited 1 MLCT state, 30 % of the molecules undergo ultrafast (150 fs) relaxation to the 3 MC state, in competition with vibrational relaxation and cooling to the relaxed 3 MLCT state. The relaxed 3 MLCT state then decays much more slowly (7.6 ps) to the 3 MC state. The 3 MC state is rapidly (2.2 ps) deactivated to the ground state. The 5 MC state is not involved in the deactivation pathway. The ultrafast partial deactivation of the 3 MLCT state constitutes a loss channel from the point of view of photochemical efficiency and highlights the necessity to screen transition‐metal complexes for similar ultrafast decays to optimize photochemical performance. Abstract : An iron(II) NHC complex was studied by sub‐picosecond X‐ray spectroscopy to identify and quantify the states involved in the deactivation cascade after light absorption. After population of a hot 3 MLCT state, 30 % of the molecules undergo an ultrafast relaxation to the 3 MC state, in competition with a slower parallel pathway over the relaxed 3 MLCT state.